Inovasi Ikan Kutuk dan Bambu Untuk Motif Batik Ciprat Langitan Simbatan Khas Magetan - Amalia Chrissafa Z; Anya Fitriadila L. A; Kahfi Amani F; Renaldi Surya S (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Batik is one of Indonesia's traditional handicrafts which has high popularity and is a cultural heritage. Until now, batik has developed motifs taken from typical regional icons. One of them is splashed batik made by people with disabilities at the Sheltered Workshop Peduli Sambung Roso which is located in Desa Simbatan , Kabupaten Magetan. Splashed batik is a motif produced from brush splashes. The innovative idea of ​​splash batik was collaborated with cursed fish and bamboo motifs. Cursed fish is a typical icon of Simbatan Village and bamboo is a typical icon of Magetan Regency. The research methods carried out started from exploration, design and realization of the cursed fish and bamboo batik motif entitled